106 CHF patients are vitamin D deficient and hyperparathyroid, with levels of each related to markers of severity. (9th June 2011) - Begg, G A; Kearney, L; Wheatcroft, A C; Byrom, R; Barnes, S; Gierula, J; Barth, J; Cubbon, R; Kearney, M T; Witte, K K
Abstract : Background: The vitamin D-parathyroid (PTH) axis is increasingly recognised as potentially being involved with many of the features of the syndrome of CHF. We wanted to explore the relationship between vitamin D and PTH levels in a group of CHF patients and relate these to markers of severity. Methods: We analysed serum 25(OH) vitamin D3 levels in 406 consecutive attendees of the Leeds Advanced Heart Failure clinic (310 men) and correlated these to clinical markers of severity. Results: Mean age (SE) was 69 (3) years, mean left ventricular ejection fraction (LVEF) 31 (2)%, mean serum creatinine 117 μmol/l (2.4), median vitamin D levels (IQR) 30 (20–43) nmol/l (normal for skeletal health>75 nmol/l) and median parathyroid levels 8.8 (6.2–13.5) pmol/l (normal<6.5 pmol/l). Aetiology was ischaemic heart disease in 63% and 23% had diabetes mellitus. Patients were optimally treated (84% on β-blockers, 88% on ACE inhibitors, and 46% on spironolactone). The mean daily dose of furosemide was 60 (3) mg. Very few patients (5%) were sufficient in vitamin D. Patients with worse symptoms as measured by NYHA status had lower vitamin D levels and higher PTH levels (Abstract 106 figures 1 and 2 ). There was also a negative relationship between furosemide dose and vitamin D (Abstract 106 figure 3 ) and, in an unselected subset of 160 patients (mean peak oxygen uptake (pVo2 ) 16.6 (0.5) ml/kg/min), there was a positive relationship between pVo2 and vitamin D (Abstract 106 figure 4 ). Patients with diabetes had lower vitamin D levels than non-diabetics (p<0.001) and there was a negative correlation between vitamin D and fasting glucose levels (r=0.13; p=0.02). There was no relationship between vitamin D levels and age, calcium, creatinine or CRP, and no differences between those patients taking and those not taking β-blockers and ACE inhibitors. In 8 unselected patients we found a negative relationship between tumour necrosis factor-alpha (TNF-α) levels and vitamin D (r=0.62; p=0.05). Although there was no relationship between vitamin D levels and baseline LVEF, in a subgroup of 150 patients followed up one year after titration to optimal CHF therapy, there was a significant positive relationship between change in LV dimensions and vitamin D levels at the time of the baseline scan (p<0.05). Conclusions: The vitamin D-PTH axis is abnormal in CHF, related to the severity of the condition. Our data suggest that reverse remodelling in response to optimal drug titration is greater in those with higher vitamin D levels. Whether vitamin D deficiency is causally related to CHF remains unknown and requires a long-term, randomised, placebo-controlled study in CHF patients with efficacy and mechanistic outcomes, using a dose of vitamin D capable of normalising both vitamin D and PTH levels.